Variant Reinterpretation in Survivors of Cardiac Arrest With Preserved Ejection Fraction (the Cardiac Arrest Survivors With Preserved Ejection Fraction Registry) by Clinicians and Clinical Commercial Laboratories. (June 2021) - Davies, Brianna; Bartels, Kirsten; Hathaway, Julie; Xu, Fang; Roberts, Jason D.; Tadros, Rafik; Green, Martin S.; Healey, Jeffrey S.; Simpson, Christopher S.; Sanatani, Shubhayan; Steinberg, Christian; Gardner, Martin; et al.
Abstract : Background: Following an unexplained cardiac arrest, clinical genetic testing is increasingly becoming standard of care. Periodic review of variant classification is required, as reinterpretation can change the diagnosis, prognosis, and management of patients and their relatives. Methods: This study aimed to develop and validate a standardized algorithm to facilitate clinical application of the 2015 American College of Medical Genetics and Association for Molecular Pathology guidelines for the interpretation of genetic variants. The algorithm was applied to genetic results in the Cardiac Arrest Survivors With Preserved Ejection Fraction Registry, to assess the rate of variant reclassification over time. Variant classifications were then compared with the classifications of 2 commercial laboratories to determine the rate and identify sources of variant interpretation discordance. Results: Thirty-one percent of participants (40 of 131) had at least 1 genetic variant with a clinically significant reclassification over time. Variants of uncertain significance were more likely to be downgraded (73%) to benign than upgraded to pathogenic (27%; P =0.03). For the second part of the study, 50% (70 of 139) of variants had discrepant interpretations (excluding benign variants), provided by at least 1 team. Conclusions: Periodic review of genetic variant classification is a key component of follow-up care given rapidly changing information in the field. There is potential for clinical care gaps with discrepant variant interpretations, based on the interpretation and application of current guidelines. The development of gene- and disease-specific guidelines and algorithms may provide an opportunity to further standardize variant interpretation reporting in the future. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT00292032. Abstract : Supplemental Digital Content is available in the text.